162 Polymersomes Functionalized with HSP70 – Novel, Synthetic Cardioprotective Nanovesicles. (3rd June 2016) - Radenkovic, Dina; Arjun, Sapna; Poma, Alessandro; Nyberg, Sophie; Battaglia, Beppe; Yellon, Derek M; Davidson, Sean
Abstract : Background: Exosomes -– nano-sized, lipidvesicles released by cells into the blood – can protect the myocardium against ischaemia/reperfusion (IR) injury. 1 This cardioprotection is mediated by heat shock protein 70 (HSP70) on the exosome surface interacting with Toll-like receptor 4 (TLR-4) on cardiomyocytes and activating intracellular protective signalling kinases. 1 Polymersomes are synthetic nanovesicles with a structural similarity to exosomes, and the capacity to function as drug delivery vehicles. Aim: The aim of this project was to develop polymersomes functionalized with HSP70 peptides as "synthetic exosomes" with a potential therapeutic application against IR injury. Methods: POEGMA-PDPA polymersomes were synthesised from hydrophilic poly[oligo (ethylene glycol) methacrylate] and poly[2-(diisopropylamino)ethyl methacrylate] blocks, and covalently functionalized with either KSTGKANKITITNDKGRLSK ("KST") or TKDNNLLGRFELSG ("TKD") peptides from HSP70. They were analysed using Nanosight LM10-HS nanoparticle tracking analysis (NTA) and dynamic light scattering (DLS). Adult rat ventricular cardiomyocytes were pre-treated with polymersomes, then subjected to simulated IR. Percentage cell death was assessed using a vital dye and fluorescent microscopy. Results: In line with previously published data, pre-incubation with recombinant HSP70 protected cardiomyocytes from simulated IR injury, significantly reducing cell death from 74+-4% to 44+-1% (P < 0.001) with maximal protection observed at 1 ng/ml HSP70 equivalent to molar concentration of 14.3 pM. Cytoprotection was blocked in the presence of TAK-242, an inhibitor of TLR4 (83+-3%). The average size of polymersomes was ~70 nm (DLS) or 80–90 nm (NTA), and they expressed ~145 peptides per polymersome. Pre-incubation with KST- or TKD- functionalized polymersomes reduced death of cardiomyocytes exposed to simulated IR from 62+-3% to 38+-4% or 42+-4% respectively (P < 0.001). Significant protection was observed even at 10 8 particles /ml, representing a concentration of 0.17 pM particles, or 0.025 pM of HSP70 peptide. No protection was recorded with non-functionalized polymersomes. Conclusion: Polymersomes with HSP70-derived peptide sequences are non-toxic to cardiomyocytes and powerfully cardioprotective in a cell model of acute IR injury. Future ex vivo and in vivo experiments are required for pre-clinical assessment of these novel nanoparticles, before potential translational application. Reference: Vicencio et al . Plasma exosomes protect the myocardium from ischemia-reperfusion injury, J Am Coll Cardiol. 2015;65(2015):1525–36